BIRDS OF HALIMUN-SALAK NATIONAL PARK, WEST JAVA, INDONESIA: ENDEMISM, CONSERVATION AND THREATENED STATUS - Dewi M. Prawiradilaga (Treubia, 2016)
Bird surveys and long-term bird monitoring in Gunung Halimun-Salak National Park were conducted between 1998 and 2009 to obtain comprehensive data on the bird species in the area. Compilation of bird data from this study and other studies have recorded a total of 271 species, which is about 53.4% of all Javan birds (507 species) or 16.9% of all Indonesian birds (1605 species). As an important bird area, Gunung Halimun-Salak National Park is home to 43 Indonesian and Javan endemic species. Among the endemics, 32 species are restricted range species. Gaps in the protection status of the bird species are discussed. The results of this study show that Gunung Halimun-Salak National Park has the highest richness of bird species in the Java-Bali region and the conservation of its endemic and threatened species should be given main priority.